(untitled) (World of finance, 2019)
Introduction. Research, development and creation of innovation as a prerequisite for a gradual transition to the fourth industrial revolution will require significant financial resources. Deficit of free public and private capital, the existence of potential risks of innovation make it difficult to attract resources for innovation and investment projects. Purpose. Identify financial support for innovation, causes inefficient investment generalize the experience of the developed of OECD countries, outline ways to improve tax legislation in Ukraine. Results. The main results of the study. In the period of 2011–2015. The main source of financing innovations were the resources of enterprises, as well as significantly reduced funding from the budget, foreign investments and other sources. Revealed that the fiscal stimulus, including the application of the tax legislation accelerated depreciation of fixed assets – not intensified investment and innovation processes. Financial resources are concentrated on providing ongoing activities, rather than on upgrading technology to the level of new technological structures. Research experience providing financial innovation in developed OECD countries and Vietnam showed that the structure of sources of financial support is of secondary importance compared to the volume of financing, the ability to attract resources for co-financing of state enterprises, financial institutions, innovation funds; the use of innovative financial instruments to attract resources. Conclusion. The process of financial support innovation offered to restore fiscal incentives to new conditions – to achieve efficiency innovation (creating an innovative product, the introduction of innovative new technologies, innovative renewal of fixed assets, etc.), targeted use of resources from the use of tax incentives and methods for accelerated depreciation.